Pengaruh Metode Pembelajaran Card Short Terhadap Peningkatan Daya Ingat Mahasiswa Pada Pembelajaran Bahasa Arab Di Lapas Pemuda Kelas II A Kota Tangerang - Nur Halimah; Aslihatul Rahmawati; Ade Holisoh (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
The purpose of this study was to determine the effect of applying the short card learning method on improving student memory. Total population of 30 students, sampling technique using saturated sampling technique. Data analysis techniques using correlation and regression analysis. The results showed that there was a significant effect on the application of the short card learning method on improving student memory. With the results of calculating the correlation coefficient with the rxy formula, the results obtained are 0.67 with a significantly strong level and are positive in the use of the short card learning method to improve student memory at the Tangerang City Youth Lapas. This is also reinforced by the tcount results obtained with a score of 4.776 which is greater than the ttable which has a value of 2.048 and 1.701. And the results of the calculation of the coefficient of determination can be seen that the independent variable, namely the card short learning method with a contribution of 44.89%, influences the dependent variable, namely increasing student memory and 55.11% is influenced by other factors that the researchers did not study carefully.Keywords: card short learning method; memory;